2019
DOI: 10.1186/s12986-019-0348-5
|View full text |Cite
|
Sign up to set email alerts
|

The effects of exercise and ambient temperature on dietary intake, appetite sensation, and appetite regulating hormone concentrations

Abstract: Background It is not clear whether the frequently reported phenomenon of exercise-induced anorexia is exacerbated or blunted in warm or cold environments. Therefore, this study investigated the effects of exercise in three different environmental temperatures vs. rest, on perceptions of appetite, appetite regulating hormones, and food intake. Methods In a randomized repeated-measures design, 18 Canadian Armed Forces members (14 male, 4 female) completed four 8-h trials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 58 publications
4
39
0
Order By: Relevance
“…Further, studies investigating food consumption after sleep restriction have not included physically demanding tasks and/or physical activity. In nonsleep restricted conditions, acute exercise does not influence immediate energy intake [37], but increased energy intake has been found 120 mins post-exercise, corresponding with increased ghrelin concentrations [65]. Current findings suggest this effect may be blunted with sleep restriction.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Further, studies investigating food consumption after sleep restriction have not included physically demanding tasks and/or physical activity. In nonsleep restricted conditions, acute exercise does not influence immediate energy intake [37], but increased energy intake has been found 120 mins post-exercise, corresponding with increased ghrelin concentrations [65]. Current findings suggest this effect may be blunted with sleep restriction.…”
Section: Discussionmentioning
confidence: 60%
“…Taken together, these findings suggest that, in sleep restricted conditions, workers may self-select snacks high in carbohydrates, fat and sugar.Compared to cold temperature, food intake may be less following physically demanding tasks in hot temperatures [36]. For example, studies have found suppressed appetite in hot temperatures compared to cooler temperatures [37][38][39]. In one study, there was no difference between energy intake post-exercise between hot and neutral temperatures [40].…”
mentioning
confidence: 99%
“…Energy and macronutrient intakes were expressed per 24 h period to compare them to the 24 h energy expenditures. The present manuscript has a companion study that provides detailed methods and results on energy expenditure and appetite-related hormones [40].…”
Section: Methodsmentioning
confidence: 99%
“…An initial blood sample (10 ml) was taken from an antecubital vein (erythrocytes and plasma were separated within 1 h of collection), and then participants were provided with the breakfast meal from their self-selected ration packs. Blood samples were taken for the assessment of plasma concentrations of nutritional biomarkers (results provided in this manuscript) and appetite hormones (leptin, acylated ghrelin, GLP-1 and PPY) (for detailed analyses on appetite hormones, see Mandic et al [40]). The visual analogue scales for appetite (VASA) [43] were administered throughout the trial (for detailed analyses, see Mandic et al [40]).…”
Section: Methodsmentioning
confidence: 99%
“…The Environmental Sensors allows the system to determine if the environmental signs are optimal for performing the exercises. They measure conditions such as temperature levels, humidity, CO2 and air quality among others, as high levels of these environmental factors can cause harmful effects when exercising [21][22][23].…”
Section: System Descriptionmentioning
confidence: 99%